The Hidden Power of Your Customers : Four Keys to Growing Your Business Through Existing Customers - Carroll, Becky, 1966- author 530052; Hart, Vanessa narrator (Hoboken, NJ. : Wiley, 2011)
"Winning strategies to keep your existing customers coming back. A business's current customer base needs to be considered among the company's most valuable assets. Discover the practical tools to preserve and grow this asset and boost your business by tapping into The Hidden Power of Your Customers. Existing customers are the key to ongoing business growth. They are the people who already know you and buy from you. Yet too many businesses allow their existing customers their least expensive, most easily acquired sales to slip away. Don't let this happen to you! Learn how to strengthen your business using social entrepreneur Becky Carroll's four keys to unleash The Hidden Power of Your Customers. This easy-to-read and practical guide features useful steps, inspirational stories, and real-world examples so you can create a customer strategy that keeps customers coming back (and telling their friends and colleagues). Reveals four keys to success: relevant marketing, orchestrated customer experience, customer-focused metrics, and killer customer service. Details a fundamental shift that needs to take place in how businesses treat their existing customers. The author writes the blog "Customers Rock!" and is the Social Media Correspondent for NBC/7 San Diego"--